Hydrostructural Pedology: A Novel Scientific Discipline for Physical Modelling of ‘Green Water’ Dynamics in Soil-plant-atmosphere System - Braudeau , Erik; Boukcim, Hassan; Assi , Amjad T.; Mohtar, Rabi H. (Research Highlights in Agricultural Sciences Vol. 3, 2022)
Using hydrostructural pedology, a new paradigm of soil characterization and modeling in agro environmental sciences, we were able to show that the “green water” concept of agronomists corresponds exactly to the pedostructural water concept which was physically defined in this new paradigm. The water in the pedostructure of soils is composed of two types of water: the micro water and the macro water. These two water pools are nested one in the other within the soil aggregates. They can either be found inside primary aggregates or outside of these aggregates in the interpedal space, depending on their chemical potential in relation to their position in the pedostructure. Using this new paradigm, a fundamental physics of the pedostructural water might be constructed. Finally, the soil medium can now be considered as the location in which the free water, blue water from rainfall or irrigation, and infiltrates by gravity through the macro pore space of the soil, is partially absorbed by the pedostructure, and becomes then the ‘green water’ of the soil. In reality, soil green water is the soil water reserve that is accessible to plant roots and is subsequently transpired into the canopy by the plants. The soil-water model Kamel®, developed based on this new paradigm, is uniquely able to physically simulate the opposite dynamic cycles of these two kinds of water (blue and green) within the soil-plant-atmosphere system, their exchanges and equilibrium states with time, at each depth of the pedon. For the sustainable development and management of agricultural zones, significant implications are offered for the strategy of soil-water characterisation, mapping, and modelling.